Implementasi Alokasi Dana Desa Di Desa Permai Kabupaten Kepulauan Meranti - Rezkia Reisa Dora (Jayapangus Press, 2021)
This research is intended to find out and describe how the implementation of the Village Fund Allocation in Permai Village, West Rangsang District, Meranti Islands Regency. The purpose of this research is to know clearly the use of Village Fund Allocation from 2019 to 2020 starting from the ADD activity process, ADD implementation, to the monitoring and evaluation stage of the ADD program. This type of research used in this study is descriptive qualitative to illustrate how the implementation of ADD in the Village of Permai, West Rangsang District, Meranti Islands District as a whole. From the results of the study, it was found that the ADD activity process was going well, but there were some programs that had not been fully realized. This is because the amount of ADD funding is considered to be very minimal given the needs in Permai Village are very large and require special attention. The results of this study have not been published anywhere.